The impact of monetary and commodity fundamentals, macro news and central bank communication on the exchange rate: evidence from South Africa - Balázs Égert (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper studies drivers of high-frequency (daily) dynamics of the South African rand vis-à-vis the dollar from January 2001 to July 2007. We find strong nonlinear effects of commodity prices, perceived country and emerging market risk premium and changes in the dollar-euro exchange rate on changes in daily returns of the rand-dollar exchange rate. We also identify a one-sided nonlinear mean reversion to the long-term monetary equilibrium. In addition we establish very short-lived effects on the exchange rate of selected macroeconomic surprises and central bank communication aimed at talking up the rand.
Keywords: E31; F31; O11; P17; 330; exchange rate; nonlinearity; commodity prices; monetary model; macroeconomic news; central bank communication; South Africa; Wechselkurs; US-Dollar; Volatilität; Zentralbank; Staatliche Information; Südafrika